KORELASI STRAIN RATE DENGAN KADAR ORGANIK PADA TEST KONSOLIDASI METODE CONSTANT RATE OF STRAIN - Wardana, I Gusti Ngurah; Widiarta, IB. (Jurnal Ilmiah Teknik Sipil, 2012)
Study on the determination of strain rate on CRS consolidation test method had been done on clay soil with different plasticity level. Similar study on organic clay soil had also been carried out, in which the study was limited on organic soil with low percentage of organic content that can be tested using CRS method, and the maximum organic content is 16 %. Up to date there is no study yet carried out using CRS method for soil with high organic content (> 16 %); therefore it has not yet known what is the strain rate range can be chosen. The problems arise if CRS method applied to organic clay soil are: what the correlation between strain rate magnitude and the organic content is; what the suitable strain rate for soil with high organic content is; whether CRS method can be used for all type of organic soil without modifying the available method. For this study, soil samples were prepared in laboratory by mixing organic soil with caolinite with different percentage of organic content, i.e. 10 %, 20 %, 30 %, 35 %, 40 %, and 45 %. The strain rate per minute chosen for the CRS consolidation test were 0,04 %/minute; 0,02 %/minute; 0,008%/minute; 0,005 %/minute; 0,002 %/minute. For obtaining correlation between organic content and strain rate, both CRS consolidation and conventional method were carried out. Test results and analyses show that the chosen strain rate and organic content influence the test period, water void stress formed at the base of the samples (UB), the effective stress occurred, and the values of Cc and Cv. The final conclusion of this study is that when compared with the conventional consolidation test method, the CRS method gives reasonably a good correlation on strain rate:0.04 %/minute for sample with 10 % organic content; 0,02 %/minute on sample with 20 % organic content; 0,008 %/minute on sample with 30 % and 35 % organic content 0,005 %/minute on sample with 40 % organic content; and 0,002 %/minute on sample with 45 % organic content. The testing time on the same strain rate increases when the soil organic content increases. It was also found that, at the same organic content the testing time increases as the the strain rate decreases.
Keywords: soil organic content, strain rate, CRS Method